Integration of Lean Six Sigma and Theory of Inventive Problem Solving for Minimizing Waste in Shuttlecock Industry - Renggarsari, Rika Risma; Garside, Annisa Kesy; Rosiani, Tyas Yuli; Saputro, Thomy Eko (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2023)
In today's competitive business world, organizations are striving to improve their operations and stay ahead. Lean Six Sigma is a popular approach that helps optimize processes and reduce waste. This research focuses on using Lean Six Sigma and TRIZ together to reduce waste in the shuttlecock industry. The study uses a structured process and tools like Value Stream Mapping and Fault Tree Analysis to find and solve waste issues. The results show problems like unnecessary activities, delays, and defects in the production process. Using TRIZ, suggestions for improvements are made based on the analysis. This study shows that combining Lean Six Sigma and TRIZ can effectively reduce waste and improve processes. The findings add to our understanding of using these methods in the shuttlecock industry and offer insights for future research and improvements.